SISTEM PERCAKAPAN VISUAL UNTUK STIMULASI ANAK USIA DINI DENGAN HAMBATAN PERKEMBANGAN BAHASA DAN BICARA - Diana Dwi Jayanti (JCE (Journal of Childhood Education), 2017)
This is a qualitative study of a case study aimed at knowing the effectiveness of visual conversation system through picture cards to stimulate early childhood development with language and communication barriers. The subjects in this study were chosen through the procedure of determining the subjects in qualitative research proposed by Sarantakos (1993, in Poerwandari 2005), namely: 1) not directed to the large number of participants but in typical cases according to the specificity of the research problem, 2) not directed to representation in terms of numbers or random events, but to context matches. Based on the above explanation, the researcher then determines the general criteria of the subjects / participants of the study as follows: 1) The subjects are early childhood of group A or B kindergarten and 2) the subjects have language and cammunication barriers. Data collection methods are through observation, interviews, and informal assessments, as well as field notes documentation. Data analysis is performed by comparing the initial condition of subjects before being stimulated with the initial condition of the subjects after stimulation is performed. The results of data analysis show that the application of visual conversation system with themed picture cards can be used to help stimulate early childhood development with language and communication barriers.